TableS4. M3 Spectral Data for Endmembers and 76 Identified Craters.xlsx - Ziyi Jia (19840452) (2024)
Data for the manuscript submitted to GRL (i.e., Mare Basalt Thickness in the Chang’E-6 Landing Region: Insights into Late-stage Volcanism in the Lunar Farside South Pole–Aitken Basin)